2021
DOI: 10.1021/acsnano.1c04142
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Mediated Nanoscale Cerium Oxide Inactivates Human Coronavirus and Rhinovirus by Surface Disruption

Abstract: The COVID19 pandemic has brought global attention to the threat of emerging viruses and to antiviral therapies, in general. In particular, the high transmissibility and infectivity of respiratory viruses have been brought to the general public’s attention, along with the need for highly effective antiviral and disinfectant materials/products. This study has developed two distinct silver-modified formulations of redox-active nanoscale cerium oxide (AgCNP1 and AgCNP2). The formulations show specific antiviral ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 51 publications
0
51
0
Order By: Relevance
“…Yet there are also reports showing no effect by CeO 2 nanoparticles on viruses. According to Neal et al [59] 200 mg/l of CeO 2 nanoparticles did not have any signi cant effect on infectivity of SARS-CoV-2 OC43 or rhinovirus RV14 after 6 h incubation. However, after doping of CeO 2 with Ag, antiviral activity of CeO 2 nanoparticles was achieved, according to authors, due to the presence of increased proportion of Ce(III) ions on the nanoparticles surface.…”
Section: Antiviral Activity Of Ceo 2 Nanoparticlesmentioning
confidence: 89%
See 1 more Smart Citation
“…Yet there are also reports showing no effect by CeO 2 nanoparticles on viruses. According to Neal et al [59] 200 mg/l of CeO 2 nanoparticles did not have any signi cant effect on infectivity of SARS-CoV-2 OC43 or rhinovirus RV14 after 6 h incubation. However, after doping of CeO 2 with Ag, antiviral activity of CeO 2 nanoparticles was achieved, according to authors, due to the presence of increased proportion of Ce(III) ions on the nanoparticles surface.…”
Section: Antiviral Activity Of Ceo 2 Nanoparticlesmentioning
confidence: 89%
“…Link et al [68] showed high binding capacity of nanoparticles of CeO 2 for nucleic acids in adeno-associated virus, adenovirus, human immunode ciency virus, and murine leukemia virus [68]. In a similar line, Neal et al [59] proposed that Ag-doped CeO 2 nanoparticles may act via physical interactions between the particles and the membrane of enveloped viruses, leading to disruption of the lipid bilayer of enveloped viruses. In case of non-enveloped viruses, the particles were proposed to interact with virion proteins.…”
Section: Disruption Of Sars-cov-2 Binding To Ace2 Receptor By Nano-ceomentioning
confidence: 99%
“…Two formulations of cerium oxide were produced with Ag modified surfaces. The physical interaction of cerium oxide nanoparticles with emerging pathogens (SARS-CoV-2, rhinovirus) leads to the disruption of lipid membrane integrity, denaturation of structural viral proteins, and virus encapsidation ( Neal et al, 2021 ).
Fig.
…”
Section: Various Potential Reported Transition Metal Oxides As Antiviral Agentsmentioning
confidence: 99%
“…Studies depicted that Sb 2 O 3 drastically reduced the growth whereas, As 2 O 3 completely inhibited viral multiplication at 10 and 12 ppm. Comparative analysis demonstrated that As 2 O 3 was much more effective to inactivate virus at lower dose of 4–8 ppm as compared to Sb 2 O 3 at 8–12 ppm ( Neal et al, 2021 ). Perovskite La x MnO 3 version (x = 1, 0.95, and 0.9) is well-known for their catalytic properties involving oxidization reactions.…”
Section: Various Potential Reported Transition Metal Oxides As Antiviral Agentsmentioning
confidence: 99%
“…In study by Neal et al (2021) authors found that silver-modified CeO 2 NPs (AgCNPs) inactivate human coronavirus OC43, and human rhinovirus 14, and has been shown to be promising potential disinfectants (Neal et al, 2021). Nefedova et al (2022) found that CeO 2 NPs with positive, and negative surface charge have significant antiviral activity against SARS-CoV-2, influenza virus A/WSN/1933, transmissible gastroenteritis virus, bacteriophage φ6, whereas they were ineffective against picornavirus EMCV, and negatively charged CeO 2 NPs were slightly active against bacteriophage MS2 (Nefedova et al, 2022).…”
Section: Introductionmentioning
confidence: 98%